Phonological Interference Forms of Filipino Language in BIPA Learning - Hepy Delinasari; Elen Inderasari (Ikaprobsi, 2023)
This study aims to describe the form of Indonesian phonological interference in Filipino students learning BIPA at the Philippine Normal University Sout Luzon. This research is a qualitative descriptive study. The data in this study are events, documents, and informants. Data collection techniques used are observation, interviews, and documentation. The data collection technique used is the purposive sampling technique. Checking the validity of the data in this study used a theoretical triangulation technique. The data analysis technique used is the equivalent technique (translational equivalent) which is combined with data collection, data reduction, data presentation, and conclusion. The results of this study found three forms of Indonesian phonological interference in Filipino students in BIPA at the Philippines Normal University Sout Luzon. The form of the interference is phonological interference with the addition of phonemes, subtraction of phonemes, and changes of phonemes.